Feeling our way to an analysis of English possessed idioms - Flickinger, Daniel (2016)
This paper describes an analysis for possessive idioms in English (e.g. I twiddle my thumbs’ “I am idle”). The analysis relies on matching at the semantic level, to allow for syntactic variation. It has been implemented in the English Resource Grammar, and tested by parsing a subset of the British National Corpus. In addition to the syntactic analysis, we have linked the idioms to entries in the Princeton Wordnet, to allow for further lexical semantic analysis